Effect of Homogenization on Microstructure Characteristics, Corrosion and Biocompatibility of Mg-Zn-Mn-xCa Alloys - Zhang, Yuan (Materials (Basel), 2018)
The corrosion behaviors of Mg-2Zn-0.2Mn-xCa (denoted as MZM-xCa alloys) in homogenization state have been investigated by immersion test and electrochemical techniques in a simulated physiological condition. The microstructure features were characterized using scanning electron microscopy (SEM), X-ray diffraction (XRD), transmission electron microscopy (TEM) and electron probe microanalysis (EPMA), and the corrosion mechanism was illustrated using atomic force microscope (AFM), X-ray photoelectron spectroscopy (XPS) and confocal laser scanning microscopy (CLSM). The electrochemical and immersion test verify the MZM-0.38% Ca owns the best corrosion performance with the corrosion rate of 6.27 mm/year. Furthermore, the film layer of MZM-0.38% Ca is more compact and denser than that of others. This improvement could be associated with the combined effects of the suitable content of Zn/Ca dissolving into the α-Mg matrix and the modification of Ca-containing compounds by heat-treatment. However, the morphologies were transformed from uniform corrosion to localized pitting corrosion with Ca further addition. It could be explained that the excessive Ca addition can strengthen the nucleation driving force for the second phase formation, and the large volumes fraction of micro-galvanic present interface sites accelerate the nucleation driving force for corrosion propagation. In addition, in vitro biocompatibility tests also show the MZM-0.38% Ca was safe to bone mesenchymal stem cells (BMSCs) and was promising to be utilized as implant materials.